Divining Practices in Mary Kingdom In (the second millennium) B.C - Shahood, Ahmad; Sakr, Reem (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
... This research sheds light over an important activity of the religious beliefs in Kingdom of Mary, which is The faith, concerning the vital role of diviners and their participation the King authority in running the citizens affairs especially, that the religious beliefs of this Kingdom was characterized by intellectual riches which was obviously appeared in its discovered texts, and which was based on trying to find out a convincing interpretation for the human mentality at that time, concerning the mysterious phenomena, in which the nature has played the main role in answering such these questionable matters. So, the research focused on the role of the diviner as a mediator between the divine symbols and the human beings through several divining practices such as, prediction, dreams analysing and setting the judgments…